Applying Service Supply Chain Management in Response to the COVID-19 Pandemic: the Case of a Thai Public Hospital - Khanchanapong, Teerasak (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2022)
During the COVID-19 pandemic, Thai hospitals have faced substantial resource constraints within their operations. Hence, this study aims at contributing to the service supply chain management (SSCM) research by proposing an SSCM model that will help public hospitals respond to the pandemic. By applying the competence-based view, SSCM processes are intra- and inter-organizational in nature and include seven major dimensions, namely (1) demand management (DM); (2) capacity and resource management (CAP); (3) customer relationship management (CRM); (4) supplier relationship management (SRM); (5) order process management (ORM); (6) service performance management (SPM); and (7) information and technology management (ITM). This model not only identifies key practices related to these dimensions but also explains how each element is related to others and how they coproduce quality medical services that satisfy patients’ needs in the right place and at the right time. This study also provides practical guidelines for public hospitals in response to the pandemic. Despite these contributions, this research was limited by time constraints and the degree of the hospital’s participation with two vice-directors involved in completing the research project, both in regard to the breadth and depth of the analysis, as well as the interpretation of the results. As a single case study using research methodology was utilized in this study, a longitudinal or experimental study is recommended to strengthen the causal inferences. Replicating and extending this study in other hospitals may also provide a basis for the external validation of the findings.